Avaliação por ressonância magnética funcional e estimulação magnética transcraniana da intervenção única da terapia espelho em pacientes após acidente vascular cerebral isquêmico - Novaes, Morgana Menezes (2012)
Mirror therapy (MT) is being used as a rehabilitation tool in various diseases, including stroke. Although some studies have shown its effectiveness, little is known about neural mechanisms that underlie the rehabilitation process. Therefore, this study aimed at assessing cortical neuromodulation after a single MT intervention in ischemic stroke survivors, by means of by functional Magnetic Resonance Imaging (fMRI) and Transcranial Magnetic Stimulation (TMS). Fifteen patients participated in a single thirty minutes MT session. fMRI data was analyzed bilaterally in the following Regions of Interest (ROI): Supplementary Motor Area (SMA), Premotor cortex (PMC), Primary Motor cortex (M1), Primary Sensory cortex (S1) and Cerebellum. In each ROI, changes in the percentage of occupation and beta values were computed. Group fMRI data showed a significant decreased in the percentage of occupation in PMC and cerebellum, contralateral to the affected hand (p <0.05). Significant increase in beta values was observed in the following contralateral motor areas: SMA, Cerebellum, PMC and M1 (p<0,005). Moreover, a significant decrease was observed in the following ipsilateral motor areas: PMC and M1 (p <0,001). In S1 a bilateral significant decrease (p<0.0005) was observed.TMS consisted of the analysis of Motor Evoked Potential (MEP) of M1 hotspot. A significant increase in the amplitude of the MEP was observed after therapy in the group (p<0,0001) and individually in 4 patients (p <0.05). Altogether, our results imply that single MT intervention is already capable of promoting changes in neurobiological markers toward patterns observed in healthy subjects. Furthermore, the contralateral hemisphere motor areas changes are opposite to the ones in the ipsilateral side, suggesting an increase system homeostasis.